Eco-friendly nanocomposites between carboxylated acrylonitrile–butadiene rubber (XNBR) and graphene oxide or graphene at low content with enhanced mechanical properties. Issue 12 (1st December 2016) - Smaoui, I.; Domatti, A.; Kharrat, M.; Dammak, M.; Monteil, G.
ABSTRACT: A crucial step in rubber nanocomposites is the homogenous dispersion of the nanofillers within the elastomer matrix. Herein, a green and modified latex co-coagulation strategy was conducted to develop high-performance nanocomposite materials based on carboxylated acrylonitrile-butadiene rubber (XNBR) latex with graphene oxide (GO) or reduced graphene oxide (RGO). Aqueous solutions with different concentrations of GO or RGO were mixed with XNBR rubber latex under vigorous magnetic stirring. The incorporation of graphene-derivative fillers in the XNBR matrix provided significant improvements in the rheological and mechanical properties compared to the unfilled rubber. Indeed, with increasing fillers loading, the maximum torque, tensile strength and crosslink density of obtained nanocomposites were found to increase. These results were correlated to the better dispersion of fillers through the matrix and, thus, to stronger interactions between the oxygen-containing functional groups of fillers and the carboxyl ones in XNBR matrix.